2019
DOI: 10.1039/c9dt01968e
|View full text |Cite
|
Sign up to set email alerts
|

New salicylaldoximato-borate ligands resulting from anion hydrolysis and their respective copper and iron complexes

Abstract: The magnetism, Mössbauer, and structural properties of a series of borate appended ligands are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…17,18 As such, the effect of having both elongation and compression distortions on the magnetic exchange between two Mn III centres has not yet been determined. Among our group's work on derivatised salicylaldoximes, [28][29][30][31][32][33][34] the crystal structure of a complex featuring two manganese coordination centres in distorted octahedral environments: one elongated and the other compressed was obtained (Fig. 1, ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As such, the effect of having both elongation and compression distortions on the magnetic exchange between two Mn III centres has not yet been determined. Among our group's work on derivatised salicylaldoximes, [28][29][30][31][32][33][34] the crystal structure of a complex featuring two manganese coordination centres in distorted octahedral environments: one elongated and the other compressed was obtained (Fig. 1, ESI †).…”
Section: Introductionmentioning
confidence: 99%
“…Our goal for this research was to investigate the relative stability of a series of transition metal complexes, specifically dinuclear homo- and heterometallic, and their associated magnetic properties. Our complex framework stems from the ligand, H 2 L (6,6′-dimethoxy-2,2’-[(1,3-propylene)dioxybis(nitrilomethylidyne)]diphenol), which was chosen as it has two distinct coordination environments (Figure ), and the literature has shown that its analogues are capable of producing polynuclear, specifically dinuclear, complexes. ,, Our group has previously reported several exciting polynuclear structures with interesting magnetic and/or structural properties. In this research, we report the synthesis, transmetalation, X-ray structures, and computational and magnetic analyses of three dimeric complexes, CuCu ( [ C u 2 I I L ( N O 3 ) 2 ] ), MnMn ( [ M n 2 I I L ( M e O H ) 2 ( N O 3 ) 2 ] ), and CuMn ([Cu II Mn II L (NO 3 ) 2 ]). The labeling of the complexes is directly related to the metal ions occupying the coordination pockets (M1M2, Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the synthesis and characterization of polynuclear derivatized salicylaldoxime clusters began in 2009 with the synthesis and structural characterization of a hexacopper trihelicate complex, [Cu 6 (μ 3 -OH 0.5 ) 2 (H 4 L -2H) 3 ]­(PF 6 ) 3 ( 1 , H 4 L = 3,3′-[ N , N ′-dimethyl-1,6-hexanediaminobis­(methylene)]­bis­[2-hydroxy-5- tert -butylbenzaldehyde oxime]) . There have been several analogous iron examples reported after the investigation of this copper complex.…”
Section: Introductionmentioning
confidence: 99%